Design of Constant Speed Controller for Hydraulic Retarder Based on Robust Control - Pengxiang Song; Ao Meng; Yang Ding (Applied Sciences)
Achieving long downhill constant-speed driving of heavy vehicles is of great significance for improving vehicle transport safety. As a kind of auxiliary brake, the hydraulic retarder has the characteristics of large braking torque and compact structure. More importantly, the hydraulic retarder is capable of braking for a long period of time, which enables the vehicle to travel downhill at a constant speed with less or no use of mechanical brakes. However, due to the complexity of hydraulic retarder braking conditions, its output braking torque presents time-varying and non-linear characteristics, and the control of the hydraulic retarder filling rate in order to achieve the vehicle’s long downhill constant-speed braking is a challenging problem. This research proposes a constant-speed control strategy utilizing the robust control method to address the issue of prolonged downhill braking at constant speed for heavy-duty vehicles, which achieves constant-speed and stable driving downhill by controlling the filling rate of the hydraulic retarder. Initially, the dynamic model of the downhill process for heavy-duty vehicles and the physical model of the hydraulic retarder are established. Then, based on the concept of sliding mode control, the sliding mode controller with saturation function and the high-frequency robust controller are developed to modulate the filling rate of the hydraulic retarder in response to variations in vehicle speed. In order to verify the effectiveness of the algorithm, three different operating conditions were set according to the vehicle mass and road gradient, and simulation tests were carried out in the MATLAB/Simulink environment. Simulation results indicate that the high-frequency controller exhibits remarkable robustness against dynamic disturbances within the system. Additionally, when variations in vehicle mass and road gradient occur, the root mean square error of the high-frequency controller’s speed, in comparison to the fuzzy controller, decreases by 0.1157 km/h, while the maximum absolute error in vehicle speed diminishes by 0.248 km/h. Simultaneously, the high-frequency controller proficiently suppresses chatter, thereby meeting the demand for consistent speed braking in big trucks on prolonged downhill gradients.